Evaluating the Effect of Positive Parent Contact on Elementary Students' On-Task Behavior. (October 2020) - Fefer, Sarah A.; Hieneman, Meme; Virga, Caitlin; Thoma, Ashley; Donnelly, Marina
Family–school partnership has consistently been associated with positive student outcomes. Unfortunately, efforts to engage parents are often demanding, with limited planning around reinforcement needed to sustain participation. The study purpose was to evaluate a behavioral approach to enhance teacher–parent communication and improve student on-task classroom behavior. Positive Parent Contact (PPC) required teachers to recognize positive behavior of a student identified for additional behavioral supports and report positive incidents to parents through two weekly emails. A multiple-baseline design was used with five participant triads (teacher, student, and parent) from two elementary schools. Visual analysis and descriptive statistics showed increased on-task behavior based on observations conducted during challenging classroom routines. Non-overlap of all pairs' effects ranged from .67 to .90, with a combined effect of .75 (Hedges g ). Results suggest that PPC improved on-task classroom behavior, and reciprocal parent–teacher communication was enhanced. Parents and teachers reported that PPC was feasible and acceptable. Limitations and implications are discussed.